(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we initiate the oscillation theory for h-fractional difference equations of the form where _a∆^α_h is the Riemann-Liouville h-fractional difference of order α, T^a_h :=a + kh, k ∈ Z^+ ∪0 , and a ≥ 0, h > 0. We study the oscillation of h-fractional difference equations with Riemann-Liouville derivative, and obtain some sufficient conditions for oscillation of every solution. Finally, we give an example to illustrate our main results.